2022
DOI: 10.2196/27310
|View full text |Cite
|
Sign up to set email alerts
|

A Google Trends Approach to Identify Distinct Diurnal and Day-of-Week Web-Based Search Patterns Related to Conjunctivitis and Other Common Eye Conditions: Infodemiology Study

Abstract: Background Studies suggest diurnal patterns of occurrence of some eye conditions. Leveraging new information sources such as web-based search data to learn more about such patterns could improve the understanding of patients’ eye-related conditions and well-being, better inform timing of clinical and remote eye care, and improve precision when targeting web-based public health campaigns toward underserved populations. Objective To investigate our hypothesis that the pub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Advances or delays shorter than 60 minutes (for example for the words "chamomile", "melatonin" and "stress") may suggest that the timing of the search query is at least partially driven by the circadian clock rather than by social timing. Diurnal variation in RSV has been previously observed [21][22][23]. For instance, a study by Zitting et al [22] found diurnal variation for the word "insomnia" with a peak in searches around 3 am, corresponding to the insomnia peak in the current study.…”
Section: Discussionsupporting
confidence: 66%
“…Advances or delays shorter than 60 minutes (for example for the words "chamomile", "melatonin" and "stress") may suggest that the timing of the search query is at least partially driven by the circadian clock rather than by social timing. Diurnal variation in RSV has been previously observed [21][22][23]. For instance, a study by Zitting et al [22] found diurnal variation for the word "insomnia" with a peak in searches around 3 am, corresponding to the insomnia peak in the current study.…”
Section: Discussionsupporting
confidence: 66%